Multizonal observational study conducted by clinical practitioners on evolocumab use in subjects with hyperlipidemia in Saudi Arabia and Kuwait: Results from the ZERBINI study - Al Faraidy, Khalid; Akbar, Mousa; Shehri, Mohamed; Aljarallah, Mohammad; Abdin Hussein, Gamal; Dashti, Raja; Al Qudaimi, Ahmad; Al Nouri, Fahad; Awan, Zuhier; Essam, Ahmed; Emara, Alaa (PloS one, 2023)
Dyslipidemia is a prevalent condition with significant morbidity and mortality across the world, including in the Arabian Gulf. The present study aimed to describe the characteristics of patients receiving evolocumab in clinical practice. ZERBINI was a multi-country, observational, retrospective/prospective study of subjects receiving evolocumab as part of routine clinical management of their hyperlipidemia. This regional publication reports on adult participants from Saudi Arabia and Kuwait who have had ≥1 dose of evolocumab before enrollment and ≤6 months' prior exposure to evolocumab. Patient characteristics and treatment persistence data were collected in addition to baseline and follow-up data up to 12 months post-evolocumab initiation. Overall, 225 patients were included from two sites, Saudi Arabia (N = 155) and Kuwait (N = 70). Mean age was comparable across sites and most patients had baseline coronary artery disease and/or hypertension. Baseline LDL-C levels (mean ± SD 3.6 ± 1.4 mmol/L in Saudi Arabia, 3.1 ± 1.4 mmol/L in Kuwait) were reduced by approximately 57%-62% in the first 6 months after evolocumab initiation (1.5 ± 1.2 mmol/L in Saudi Arabia [n = 63], 1.2 ± 0.8 mmol/L in Kuwait [n = 28]). This decrease was maintained over the 12-month follow-up period. Most patients achieved ACC 2018 LDL-C goals (<1.8 mmol/L; 74.6% in Saudi Arabia, 93.1% in Kuwait) and ESC 2019 LDL-C goals (<1.4 mmol/L; 66.7% in Saudi Arabia, 75.9% in Kuwait) in the first 6 months after evolocumab initiation. Medication persistence with evolocumab was high (up to 90.7%). Evolocumab had a favorable safety profile and no treatment-emergent adverse events were observed at either site. Evolocumab is an effective lipid-lowering treatment in local populations. LDL-C goal achievement is increased when evolocumab is added to background lipid-lowering therapy with high tolerability and persistence. Long-term follow-up and large-scale data are needed to further support these observations.